2022
DOI: 10.1088/1361-6560/ac8593
|View full text |Cite
|
Sign up to set email alerts
|

A multi-layer strip ionization chamber (MLSIC) device for proton pencil beam scan quality assurance

Abstract: Objective: Proton pencil beam scanning (PBS) treatment fields needs to be verified before treatment deliveries to ensure patient safety. In current practice, treatment beam quality assurance (QA) is measured at a few selected depths using film or a 2D detector array, which is insensitive and time-consuming. A QA device that can measure all key dosimetric characteristics of treatment beams spot-by-spot within a single beam delivery is highly desired. Approach: We developed a multi-layer strip ionization chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…However, this approach requires a considerable amount of numerical experiment time. Future investigation will likely focus on developing advanced validation experiments using human-mimicking phantoms and state-ofthe-art instrumentation 44 to quantify proton range uncertainty. Then the experiment data can be used to identify which DL models can work compatibly, effectively, and robustly with the proposed image-guided framework for proton FLASH radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach requires a considerable amount of numerical experiment time. Future investigation will likely focus on developing advanced validation experiments using human-mimicking phantoms and state-ofthe-art instrumentation 44 to quantify proton range uncertainty. Then the experiment data can be used to identify which DL models can work compatibly, effectively, and robustly with the proposed image-guided framework for proton FLASH radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…MatriXX PT (IBA dosimetry, Germany) was used to measured dose imaging with a 7x7 mm 2 pixel resolution. The state-of-the-art multilayer strip ionization chamber (MLSIC) detector [18] was used to provide four-dimensional (4D) measurement in a spatiotemporal domain. The time and spatial resolutions of MLSIC were 320 µs and 2 mm with the active area of 256x256 mm 2 .…”
Section: Ct Scan Phantom and Detectormentioning
confidence: 99%
“…For real-time monitoring with higher dose rates, NaI is susceptible to PG count saturation (Haertter et al 2021). More recently, strip ionization chambers are becoming popular for real-time monitoring (Zhou et al 2022, Yang et al 2022. Yang et al successfully demonstrated the feasibility of FLASH beam monitoring up to a 20 kHz sampling rate using a 2D strip ionization chamber.…”
Section: Introductionmentioning
confidence: 99%